DETERMINATION OF HIDDEN LAWS IN THE SELECTION OF WHEAT VARIETIES USING THE INTERVAL METHOD - Madrakhimov, Shavkat; Shodiyev, Fayzulla (Innovatsion texnologiyalar, 2024)
In the article, the ordered values of the quantitative features describing the objects of samples of soft wheat varieties are divided into intervals based on the compactness check. Also, the issue of solving the problem of dividing the wheat varieties into intervals based on the compactness hypothesis was considered. The aim is to calculate the weights of the features of wheat varieties and to distinguish among them those with the highest weight. In order to divide features into intervals, a sample of objects divided into classes was taken and a criterion was used based on intra-class similarity and interclass differences. The sample formed according to the recommendations of experts was smoothing and latentized. Weights of features were calculated for each of the resulting samples. As a result, informative features were identified that significantly contribute to the selection of wheat varieties with high grain quality. The main idea of the article is to implement new approaches to the seed sector of agriculture through the use of innovative technologies. The obtained results serve to increase productivity in this sphere and reduce costs and human labor.